Narrative approach to understand people's comprehension of acquaintance rape: The role of Sex Role Stereotyping. Issue 2 (3rd April 2022) - Stirling, Jade L.; Hills, Peter J.; Wignall, Liam
ABSTRACT: One of the most unreported crimes is acquaintance rape. This may be the result of people's understanding of what rape is because of their rape script and their stereotypes of  victim characteristics. These judgements may be moderated by sex-role stereotyping (SRS). We utilised a narrative approach to understand low and high SRS participants' rape scripts. Young-adult participants described what they believed a typical rape was, followed by describing an acquaintance rape and then what they believed the stereotypical victim of each crime would be. A narrative analysis was conducted on the data. We found that the blitz script is still held by 44% of low SRS and 47% of high SRS people despite 90% of rapes being committed by an acquaintance. While acquaintance rape scripts existed, the emotional imagery and content of these depended on participants level of SRS. Stereotypical victim characteristics also depended on SRS: those with high SRS were more likely to endorse rape myth ideals in describing victims than those with low SRS. These results have implications for educating people about what rape is so that victims might feel more confident in reporting rape.